Carcinogenic Helicobacter pylori Strains Selectively Dysregulate the In Vivo Gastric Proteome, Which May Be Associated with Stomach Cancer Progression - Noto, Jennifer M. (Mol Cell Proteomics, 2019)
Helicobacter pylori is the strongest risk factor for gastric cancer. Initial interactions between H. pylori and its host originate at the microbial-gastric epithelial cell interface, and contact between H. pylori and gastric epithelium activates signaling pathways that drive oncogenesis. One microbial constituent that increases gastric cancer risk is the cag pathogenicity island, which encodes a type IV secretion system that translocates the effector protein, CagA, into host cells. We previously demonstrated that infection of Mongolian gerbils with a carcinogenic cag(+) H. pylori strain, 7.13, recapitulates many features of H. pylori-induced gastric cancer in humans. Therefore, we sought to define gastric proteomic changes induced by H. pylori that are critical for initiation of the gastric carcinogenic cascade. Gastric cell scrapings were harvested from H. pylori-infected and uninfected gerbils for quantitative proteomic analyses using isobaric tags for relative and absolute quantitation (iTRAQ). Quantitative proteomic analysis of samples from two biological replicate experiments quantified a total of 2764 proteins, 166 of which were significantly altered in abundance by H. pylori infection. Pathway mapping identified significantly altered inflammatory and cancer-signaling pathways that included Rab/Ras signaling proteins. Consistent with the iTRAQ results, RABEP2 and G3BP2 were significantly up-regulated in vitro, ex vivo in primary human gastric monolayers, and in vivo in gerbil gastric epithelium following infection with H. pylori strain 7.13 in a cag-dependent manner. Within human stomachs, RABEP2 and G3BP2 expression in gastric epithelium increased in parallel with the severity of premalignant and malignant lesions and was significantly elevated in intestinal metaplasia and dysplasia, as well as gastric adenocarcinoma, compared with gastritis alone. These results indicate that carcinogenic strains of H. pylori induce dramatic and specific changes within the gastric proteome in vivo and that a subset of altered proteins within pathways with oncogenic potential may facilitate the progression of gastric carcinogenesis in humans.